PENGARUH PEMBELAJARAN BERDIFERENSIASI TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN PRESTASI BELAJAR IPAS SISWA SD DI KECAMATAN SRUMBUNG - Euis Rosmalina; Dwi Winarsih; Siti Julaeha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the effect of differentiated learning on critical thinking skills and academic achievement in IPAS among fifth-grade students in Srumbung Subdistrict, Magelang Regency. The study aims to enhance students' critical thinking and academic performance through instructional approaches that accommodate diverse learning needs. This quantitative research employs a survey method with 94 students aged 11 to 13 from eight elementary schools with Guru Penggerak. Data were collected using a Likert scale for differentiated learning, essay tests for critical thinking, and multiple-choice tests for academic achievement. Data analysis includes normality, linearity, and multicollinearity tests, followed by regression and hypothesis testing using t-tests and the coefficient of determination. The findings reveal that differentiated learning significantly influences students' critical thinking and academic achievement. These results emphasize the importance of implementing differentiated instruction in elementary schools to improve learning outcomes. This study provides insights for educators in adopting effective teaching strategies that support diverse student needs and foster better learning experiences. Keywords: Differentiated learning, critical thinking, academic achievement,